POLA PERJALANAN PENDUDUK PINGGIRAN MENUJU KOTA SURAKARTA DITINJAU DARI ASPEK SPASIAL DAN ASPEK ASPASIAL - Aditama, Kharisma Narendra; Soedwiwahjono, Soedwiwahjono; Putri, Rufia Andisetyana (Universitas Sebelas Maret Surakarta, 2016)
: The city of Surakarta as a region which continues to undergo development has become an attraction for residents around the city core. Surakarta City which was originally not crowded will developed rapidly into densely populated area,Â impact of the process ofÂ trip that conducted by trip doers from suburban to the city core in particular. This would cause due to increasing interaction between suburban area with city core which also have impacts on traffic and population density especially for Surakarta as the city core.This research was conducted to know the characteristics of the trip patterns of suburban residents to Surakarta City so it will be described how the process of trip conducted by suburban residents to Surakarta City, and from that process of trip can be known proper management to overcome problems especially the transportation problems in Surakarta City and the surrounding areas. This research included in descriptive research which illustrates and describes a specific condition from the certain object, in this case will be portrayed in descriptive how the characteristics of the process of trip conducted by suburban residents that happened.The result of this research is based on the purpose of trip dominated by the purpose to working at 47% residents followed by the purpose to education at 27% and the purpose to shopping at 26%. Then based on income level dominated by residents with income level less than 1.145.000 rupiah, majority of residents already have private vehicles and age of trip doers dominated by 15-40 years regarded as productive age. Based on trip distribution is known that land use domination in Surakarta City is trade and services, and based on route march dominated by people pass the south area of Surakarta City and this case will trigger traffic density and the changes of space function in region of Surakarta City.